2021
DOI: 10.1097/xeb.0000000000000294
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of needle-stick injury among nurses in an acute ward of a hospital: a best practice implementation project

Abstract: This evidence implementation project aimed to identify barriers leading to needle-stick injuries (NSIs) and to develop implementation strategies to prevent NSIs in the acute ward of a hospital in central Taiwan. Introduction:The incidence rate of NSIs was 5.6% in the acute ward of a hospital in Taiwan. NSIs commonly occur during the drawing of blood, intravenous insertion, needle recapping, or performing any procedure involving sharp medical devices. NSIs are critical occupational risks among healthcare worker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The study also discovered that participants take a thorough history, such as when treatment was initiated and whether it is the treatment that is causing the OM, and also perform a physical assessment. This revelation supports a clinical audit among nurses in Taiwan for the prevention and treatment of oral mucositis among patients with cancer in the haematology–oncology setting, researchers Huang et al (2020) found that compliance with ongoing assessment of the oral cavity throughout cancer therapy trajectory was essential measures in identifying patients who will develop OM.…”
Section: Discussionmentioning
confidence: 63%
“…The study also discovered that participants take a thorough history, such as when treatment was initiated and whether it is the treatment that is causing the OM, and also perform a physical assessment. This revelation supports a clinical audit among nurses in Taiwan for the prevention and treatment of oral mucositis among patients with cancer in the haematology–oncology setting, researchers Huang et al (2020) found that compliance with ongoing assessment of the oral cavity throughout cancer therapy trajectory was essential measures in identifying patients who will develop OM.…”
Section: Discussionmentioning
confidence: 63%
“… 25 Also in this study, 36.8% of healthcare professionals never recapped needles after use, which is lower than a study reported from Taiwan increasing from 47% to 85% of participants who never recapped needles after use in their working environment. 29 The reason may be a direct shuffling of the dry needlestick by needle cap and properly disposing of the safety box.…”
Section: Discussionmentioning
confidence: 99%
“…Further advancements have been made in safety precautions with safety-engineered syringes. These include syringes made with shields or syringes with retractable needs that retract following use [ 21 ].…”
Section: Reviewmentioning
confidence: 99%